Reversible conduction block in peripheral nerve using electrical waveforms. Issue 1 (January 2018) - Bhadra, Niloy; Vrabec, Tina L; Bhadra, Narendra; Kilgore, Kevin L
Introduction: Electrical nerve block uses electrical waveforms to block action potential propagation.Materials & Methods: Two key features that distinguish electrical nerve block from other nonelectrical means of nerve block: block occurs instantly, typically within 1 s; and block is fully and rapidly reversible (within seconds).Results: Approaches for achieving electrical nerve block are reviewed, including kilohertz frequency alternating current and charge-balanced polarizing current. We conclude with a discussion of the future directions of electrical nerve block.Conclusion: Electrical nerve block is an emerging technique that has many significant advantages over other methods of nerve block. This field is still in its infancy, but a significant expansion in the clinical application of this technique is expected in the coming years.